The study of spring wheat hybrids on yield and protein content - L. B. Volkova (Аграрная наука Евро-Северо-Востока)
Spring wheat F2-F4 hybrids and their original forms were studied on yield and protein content in grain. The productivity of varieties and hybrids were highly varied depending on the environmental conditions and cross combinations (average yield is 217 g/m2, coefficient of variation 39%). The high heterogeneity of F2-F3 populations, strong modification variability and low repeatability of the trait in the offspring does not allow to judge the productive value of hybrid combinations in the first stages of selection with a sufficient degree of reliability. At crossing of varieties with contrast productivity hybrids of the second and third generations have turned to the best parent. The most high-yield samples Ferrugineum 69-96 х Pamyati Ryuba (266 g/m2), Anyuta х Stepnaya 1 (237 g/m2), Anyuta х Izida (239 g/m2) were characterized by a higher degree of variability of the trait (CV = 40...57%). Differences of genotypes on protein content in grain are well expressed. Hybrids had, as a rule, an intermediate position between the original forms. The best combination obtained in crosses of high quality varieties: Ferrugineum 69-96 х Anyuta (12.8...14.1%), Hja 23361 х Anyuta (13.3...14.0%), Botanicheskaya 3 x Gutler (12.5...15.1%), Anyuta x Engelina (12.6...15.3%). Promising hybrid combinations can be evaluated as early as F2 since the protein content is characterized by a high heritability. A high negative correlation between productivity and protein content makes it difficult to obtain initial material which combines these features at a high level. Promising hybrid combinations with optimal display of traits are selected for further breeding work: Botanicheskaya 3 x Kinel'skaya Otrada, Botanicheskaya 3 x Pamyati Ryuba, Anyuta x Engelina , Anyuta x Izida.